2010
DOI: 10.1007/s00330-010-1742-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of renal tumours: diagnostic accuracy of contrast-enhanced ultrasound for early detection of residual tumour

Abstract: CEUS has high specificity for the early diagnosis of residual tumour after renal RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 25 publications
1
49
0
1
Order By: Relevance
“…CEUS also increased the conspicuity of less defined / invisible lesions, issue demonstrated for hepatic tumours [51,52]. It has been also demonstrated that CEUS accurately depicts the vascularized, active parts in partially ablated renal tumours [16].…”
Section: Optimisation Of Percutaneous Renal Biopsymentioning
confidence: 98%
See 1 more Smart Citation
“…CEUS also increased the conspicuity of less defined / invisible lesions, issue demonstrated for hepatic tumours [51,52]. It has been also demonstrated that CEUS accurately depicts the vascularized, active parts in partially ablated renal tumours [16].…”
Section: Optimisation Of Percutaneous Renal Biopsymentioning
confidence: 98%
“…CEUS has proved to be a useful tool for the assessment of the treatment ( fig 5) [15]. In a series of patients with renal tumours treated by RFA in whom a prevalence of residual disease of 19% was documented, the sensitivity and specificity of CEUS in early detection of residual tumours was 64% and 98 %, respectively [16].…”
Section: Monitoring Of Renal Lesions Treated By Percutaneous Ablationmentioning
confidence: 99%
“…However, CEUS had lower sensitivity than that of CT/ MRI, and had worse image quality at the upper renal poles and at the periphery of the treated areas. Hoeffel et al also noted that CEUS performed better in the assessment of hypervascular tumors, a concept that has been noted in several other studies and could be related to the ability of UCAs to image the microvasculature (6,9,12). Other limitations of CEUS may include lesion location as well as the specific properties of UCAs when used in the kidneys.…”
Section: Ceus-guided Rfamentioning
confidence: 85%
“…However, unlike MRI, CEUS can be used in patients with arthroprosthesis or pacemakers, and faces less of a problem of movement artifacts from patients who cannot stay still (9). Furthermore, there has been mounting concern about the use of gadolinium MRI contrast agents in patients with chronic renal failure and how it may be associated with nephrogenic systemic sclerosis (6,9).…”
Section: Ceus Of Renal Massesmentioning
confidence: 99%
See 1 more Smart Citation